A review of the implementation of the prevention of mother-to-child transmission program in the George sub-district, Western Cape - Schaefer, Rachel (Stellenbosch : Stellenbosch University, 2017)
Introduction The most common cause for HIV infection in children in developing countries is the vertical transmission of HIV from mother to child. Without any intervention the vertical transmission rate from mother to child will be between 15-50%, depending on a number of factors. An effective prevention of mother-to-child transmission (PMTCT) program can dramatically reduce this transmission rate to as low as 2-5%. There appears to be a gap between PMTCT policy guidelines and actual implementation, and while the reasons for this are multi-factorial, one facet may be local shortfalls in the program. Aim: To review the implementation of the PMTCT program in the George sub-district for 2010. Objectives: To assess whether the PMTCT program is being conducted according to established provincial protocol; to describe possible local shortfalls in the PMTCT program; to make recommendations to improve the identified shortfalls. Methods A retrospective descriptive study, based on a record review of patient files, the PMTCT register, and birth registers in the labour ward of George provincial hospital. Every HIV positive pregnant woman from the George sub-district who delivered at the George provincial hospital obstetric unit during 2010 was included. Missing files and medical records were excluded. Data was collected from each record in the registers according to set criteria, and entered into a Microsoft Excel data sheet. Results 95% of women in the study had an HIV test at the clinic, and 93% had a CD4 count. This shows good initial uptake and acceptance of the program. However, 28% did not receive adequate antenatal PMTCT cover, 33% of patients who required highly active antiretroviral treatment (HAART) did not receive it, and 34% of women did not receive adequate PMTCT cover during labour. 86% of babies received their initial PMTCT medication within 72 hours of birth. The one month zidovudine treatment for babies (before October 2010) and six weeks nevirapine treatment (after October 2010) was not documented in 30% and 74% of cases respectively. Discussion While many aspects of the PMTCT program are being well applied in the George sub-district, there are significant shortfalls in the implementation of the program. These need to be addressed to ensure optimal prevention of HIV transmission from mother to child. Particular points which need to be focused on are improved record keeping, increasing the percentage of HIV positive women receiving adequate antenatal and intrapartum PMTCT, and increasing the percentage of HIV positive women receiving HAART.